The Influence of Pancasila Education Management, Citizenship, and Religion on Learning Interest of the Students - Arcadius Benawa (Institut Agama Islam Negeri (IAIN) Curup, 2022)
As it is known that the current Minister of Education and Culture, Nadiem Makarim, is promoting courses which are commonly called general basic courses into compulsory curriculum subjects. Therefore, this research is motivated by the concerns of education management for students who attend Pancasila Education, Citizenship Education, and Religion Education courses which are suspected of being less interest to students. Therefore, this study will see how much the influence of management of Pancasila Education, Citizenship Education, and Religion Education on the students' interest in learning, so that further steps can be taken to increase the students’ interest in Pancasila Education, Citizenship Education, and Religion Education courses. This research was also conducted as a reference material for lecturers to improve their education management in teaching students for Pancasila, Citizenship, and Religion Education courses. The results of this study indicated that there is a significant influence of the Management of Pancasila Education, Citizenship Education, and Religion Education on the students’ interest in learning. Therefore, it is very relevant and urgent for lecturers of Pancasila, Citizenship, and Religion Education to increase the students’ interest in learning through better education management.